Tatalaksana Perdarahan Pasca Tonsilektomi - Afna Adelya Siswandi; Baluqia Iskandar Putri (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Tonsillitis is an inflammation of the pharyngeal tonsils, commonly caused by viral infections, and typically resolves on its own without medical intervention. The first-line treatment for tonsillitis generally involves supportive care, such as analgesics and hydration, to alleviate symptoms. However, in cases of chronic or severe tonsillitis that cannot be managed conservatively, tonsillectomy is the recommended surgical procedure. Tonsillectomy is typically performed by an ENT specialist, and candidates for this surgery must meet the absolute and relative criteria outlined in the 2004 Health Technology Assessment (HTA) Indonesia clinical guidelines. Although tonsillectomy is a common procedure, one of the serious complications that can arise post-surgery is hemorrhage, which can lead to fatal consequences if not managed appropriately. Post-tonsillectomy bleeding is a significant cause of mortality and requires immediate and effective management. Effective management of post-tonsillectomy hemorrhage is crucial to prevent life-threatening situations that may develop without appropriate intervention. Bleeding can be addressed through close observation, bedside interventions, or additional surgery if necessary, with the initial focus on stabilizing the patient's hemodynamics and controlling active bleeding. Given the high incidence and severity of post-operative bleeding, it is vital for healthcare professionals to identify patients who experience this complication and those at high risk, providing timely and appropriate interventions to reduce the risk of fatality. Therefore, in-depth knowledge of post-tonsillectomy hemorrhage management is essential for ENT specialists in daily clinical practice.